Land surface transformation due to human activitie and its relation to climate change - Carvajal, Andrés Felipe; Pabón, José Daniel (Sociedade & Natureza, 2016)
Land cover transformations are considered global change processes, because they have the ability to affect the functioning of the planet. Many research studies have focused on the evaluation of land cover and land use, because they are factors having the footprint of some human society activities, and because its correlation with climatic variables could evidence the alterations that the action of the anthroposphere has generated on climate at different scales. This paper describes the concepts of land cover and land use, analyzes their relationship with climatic variables and presents a review of the methods used to assess the impacts of land cover and land use change on climate, highlighting three main approaches that differ from each other due to the use of data from climatological stations, remote sensing products or climate models.